Study of trinucleotide expansions and expression of androgen receptor in infertile men with abnormal spermogram referred to Royan institute. (28th August 2018) - Borjian Boroujeni, Parnaz; Firouzi, Vida; Zari Moradi, Shabnam; Mokhtari, Pegah; Dehghankhalili, Faezeh; Mollaahmadi, Fahimeh; Gourabi, Hamid; Sadighi‐Gilani, Mohammad Ali; Sabbaghian, Marjan; Mohseni‐Meybodi, Anahita
Abstract: Androgen receptor (AR) mediates androgen activities such as the growth of accessory sex organs, and initiation and promotion of spermatogenesis. There are two trinucleotide polymorphisms (CAG and GGN repeats) in the first exon of AR gene that their association with infertility is still controversial. The variants of both polymorphic repeats were investigated by PCR‐Sequencing in 220 infertile men (80 azoospermic, 60 oligospermic and 80 asthenospermic) and 80 healthy fertile controls. AR Expression level was quantified by RT‐qPCR on 30 patients (20 patients with nonobstructive azoospermia (NOA) and 10 obstructive azoospermia patients as controls). Our results demonstrated that the medians of CAG and GGN repeats length in infertile group were significantly higher than fertile men ( p  < 0.05). AR expression results showed a significant increase in SCOS group compared to control ( p  < 0.05). Long stretches of tandem repeats of AR gene may negatively affect the function of the gene and consequently lead to male infertility. In patients with SCOS, AR expression increases because of the lack of germ cells. Therefore, with increasing AR expression, the probability of SCOS occurrence is also increased. It can be concluded that increasing AR expression in testes tissue decreases the probability of sperm presence.